Pengaruh Penggunaan Abu Terbang Dan (Bestmittel) Terhadap Kuat Tekan Mortar Mutu Tinggi - Qolbilla, Ratna; Pranowo, Dadang Dwi; Khomari, Moh. Galuh; Santoso, Catur Bejo; Utanaka, Ahmad (Journal of Applied Civil Engineering and Infrastructure Technology, 2025)
High-grade mortar is a mortar that has very dense material characteristics with compressive strength reaching more than 150 MPa; the use of this mortar can strengthen the building. Increasing the strength of mortar by looking for grain size gradations that can fill the space. In this study, a mixture of normal mortar with fly ash waste additives and Bestmittel is used, which is expected to help improve quality and achieve the desired compressive strength. The tests carried out were compressive strength tests on 0.5% Bestmittel variations and fly ash variations of 0%, 10%, and 20% by weight of cement. Tests were carried out at the ages of 3, 14, and 28 days. The results showed that the effect of adding the proportion of fly ash and bestmittel to mortar according to SNI 2002 can be categorized as high quality mortar, with a compressive strength value at the age of 28 days in the 10% variation (FAB-10%) of 42.96 MPa, and 20% variation (FAB-20%) of 47.58 MPa. Therefore, the use of fly ash with bestmittel additives and the type of age shows a higher compressive strength value due to the fine grains in fly ash, and bestmittel can accelerate the hardening.